1996
DOI: 10.1152/jappl.1996.81.6.2658
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training affects myosin heavy chain phenotype in regenerating fast-twitch muscle

Abstract: The aim of this study was to analyze the effects of treadmill training (2 h/day, 5 days/wk, 30 m/min, 7% grade for 5 wk) on the expression of myosin heavy chain (MHC) isoforms during and after regeneration of a fast-twitch white muscle [extensor digitorum longus (EDL)]. Male Wistar rats were randomly assigned to a sedentary (n = 10) or an endurance-trained (ET; n = 10) group. EDL muscle degeneration and regeneration were induced by two subcutaneous injections of a snake toxin. Five days after induction of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 35 publications
(59 reference statements)
2
28
0
Order By: Relevance
“…Muscle mass growth (Esser and White 1995) and accumulation of mature (slow) myosin isoform or MHC-1 were decreased by hypokinesia and hypodynamia applied during regeneration of soleus muscle (Bigard et al 1996b;Esser and White 1995). Studies also reported that endurance exercise aects the muscle variables during regeneration (Bigard et al 1996a;Clark et al 1989;Esser and White 1995;White et al 1984). Running on a treadmill enhances the mass and the oxidative metabolism of the regenerating soleus (Clark et al 1989;White et al 1984) and causes a shift from type MHC-2b to type MHC-1 in a regenerating fast-twitch muscle (Bigard et al 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle mass growth (Esser and White 1995) and accumulation of mature (slow) myosin isoform or MHC-1 were decreased by hypokinesia and hypodynamia applied during regeneration of soleus muscle (Bigard et al 1996b;Esser and White 1995). Studies also reported that endurance exercise aects the muscle variables during regeneration (Bigard et al 1996a;Clark et al 1989;Esser and White 1995;White et al 1984). Running on a treadmill enhances the mass and the oxidative metabolism of the regenerating soleus (Clark et al 1989;White et al 1984) and causes a shift from type MHC-2b to type MHC-1 in a regenerating fast-twitch muscle (Bigard et al 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…The muscles of mdx mice are characterized by cycles of muscle fiber necrosis followed by regeneration [Haslett et al, 2005]. The regenerating fibers can be easily identified, because they contain conspicuous internal (central) myonuclei [Bigard et al, 1996]. Williams et al [1993] reported that fibers with either a predominantly centrally located string of myonuclei or a combination of central nuclei and a peripheral pattern of nuclei were noted in soleus muscle fibers of mdx mice.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this observation did not reach statistical significance (TG versus CON plantaris: P > 0.05) because of the rapid regeneration of muscle tendon and adhesion of the muscle to surrounding tissues (Goldberg, 1967;Jakubiec-Puka et al 1992). It appears that regenerating fast muscles (the present study ;Bigard et al 1996a) seem to adapt their MyHC expression to increased muscular activity (mechanical overload, locomotion activity) in the same way as mature muscle (Kandanrian et al 1992;Bigard et al 1996a;Harridge, 1996). The effect of tenotomy of the synergistic gastronecmius on regenerating slow muscle seems different from that on the regenerating fast muscle since the relative level of MyHC_1 (the most abundant MHC) was decreased in TG soleus (overloaded regenerating soleus).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, to our knowledge only one study has analysed the effects of muscular activity on the MyHC expression of a regenerating fast muscle. Bigard et al (1996a) demonstrated that an increased level of locomotion activity (running on a treadmill) modulated the expression of MyHC in the regenerating fast muscle. Thus there is a need for further inquiry into the effects of variation in muscular activity on the MyHC phenotype of fast regenerating muscles.…”
mentioning
confidence: 99%